Amine/Hydrido Bifunctional Nanoporous Silica with Small Metal Nanoparticles Made Onsite: Efficient Dehydrogenation Catalyst - Zhu, Yang; Nakanishi, Takahiro; Kanamori, Kazuyoshi; Nakanishi, Kazuki; Ichii, Shun; Iwaida, Kohji; Masui, Yu; Kamei, Toshiyuki; Shimada, Toyoshi; Kumamoto, Akihito; Ikuhara, Yumi H.; Jeon, Mina; et al. (American Chemical Society, 2017)
Multifunctional catalysts are of great interest in catalysis because their multiple types of catalytic or functional groups can cooperatively promote catalytic transformations better than their constituents do individually. Herein we report a new synthetic route involving the surface functionalization of nanoporous silica with a rationally designed and synthesized dihydrosilane (3-aminopropylmethylsilane) that leads to the introduction of catalytically active grafted organoamine as well as single metal atoms and ultrasmall Pd or Ag-doped Pd nanoparticles via on-site reduction of metal ions. The resulting nanomaterials serve as highly effective bifunctional dehydrogenative catalysts for generation of H-2 from formic acid.
Keywords: FORMIC-ACID; PD; REDUCTION; GROWTH; THIOL; XPS